Unsafe Standardization. - Thomas, Martyn (Computer (00189162), 2007)
The article discusses safety standards for software. Safety cannot be measured in isolation, but only in the context of actual operating environments. A systems approach to safety focuses on three key areas. First, any safety claims must be explicit with respect to the claim made and operating environment assumed. Next, claims must be supported by solid evidence, not just general-purpose recommendations. Finally, software design should avail itself of the industry's collective safety-related expertise.